2019
DOI: 10.1002/acm2.12754
|View full text |Cite
|
Sign up to set email alerts
|

A suggested method for setting up GSI profiles on the GE Revolution CT scanner

Abstract: Abstract“GSI Assist” is the automatic exposure control (AEC) system for dual‐energy acquisitions on the GE Revolution CT scanner. This paper describes the user options of GSI Assist, and describes the method developed at UAB Medical Center to simplify the use of GSI Assist without adversely affecting the AEC Operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recently, some researchers have found that the reconstruction of monochromatic energy images (MonoE) by spectral CT can reduce metal artifacts [ 17–19 ]. The spectral CT can be achieved by various techniques, such as rapid kVp switching (80 and 140 kVp) [ 20 ], dual source [ 21 ] and detector or dual-layer detector [ 22 ]. The synthetic MonoE can be used to reduce beam hardening artifacts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have found that the reconstruction of monochromatic energy images (MonoE) by spectral CT can reduce metal artifacts [ 17–19 ]. The spectral CT can be achieved by various techniques, such as rapid kVp switching (80 and 140 kVp) [ 20 ], dual source [ 21 ] and detector or dual-layer detector [ 22 ]. The synthetic MonoE can be used to reduce beam hardening artifacts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The small and the large phantom setups were scanned with a diagnostic DECT scanner ( Revolution Apex , GE Healthcare, Waukesha, WI, USA) equipped with a flat radiotherapy couch top ( OGS‐4 , Diacor Inc., West Valley City, UT, USA) using the FKS‐scan mode, with the maximum circular 50 cm (scan and display) field‐of‐view. The scans were acquired, with a fixed tube current for each phantom setup, which were selected by the scanner software based on the attenuation in the localizer radiographs and the noise index of the protocol 55 . Detailed scan and reconstruction parameters are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The scans were acquired, with a fixed tube current for each phantom setup, which were selected by the scanner software based on the attenuation in the localizer radiographs and the noise index of the protocol. 55 Detailed scan and reconstruction parameters are presented in Table 2. Separate water and iodine MD image series were reconstructed, as well as a VM image series saved as GSI Data Files.…”
Section: Ct Imagingmentioning
confidence: 99%
“…All patients were scanned in a second-generation multi-detector CT (Revolution CT ES, GE Healthcare, Milwaukee, Brookfield, WI, USA). For group A, scanning parameters were as follows: dual-energy helical scanning with 80/140 peak kV (kVp) fast switching with an automatic exposure control (GSI Assist, GE Healthcare, Milwaukee, WI, USA) and a noise index of 13, rotation time of 0.5 s, pitch of 0.992, slice thickness of 3 mm, and beam width of 80 mm [18]. For group B, conventional non-contrast images were acquired with 120 kVp, AutomA function (range: 80-600 mA) with a noise index of either 13 or 18, rotation time of 0.5 s, helical pitch of 0.992, slice thickness of 3 mm, and beam width of 80 mm.…”
Section: Computed Tomography Acquisitionmentioning
confidence: 99%